Molding material and method for producing same

By forming a carbon-ceramic outer layer on the inner layer of the carbon-based material, combined with silicon penetration treatment, the problem of limited scope of the carbon-based disc brake disc brake disc development and the effect of light, wear resistance and widespread application Essence

CN119384564APending Publication Date: 2025-01-28FRENI BREMBO SPA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380045669.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-07
Filing Date
2023-06-01
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Disc brake discs made of existing carbon-based materials are prone to wear at the brake belt, resulting in carbon particles emissions and limited application range; while discs made of carbon-ceramic materials lose their lightweight characteristics and are difficult to process.

Method used

The inner layer made of carbon-carbon material and a forming material composed of carbon and silicon carbide materials is used to form a carbon-ceramic outer layer by silicon penetration, combined with the lightweight and light quality of "C/C" materials Thermal conductivity.

Benefits of technology

The light quality and thermal conductivity of the carbon-based materials have been realized, and the wear resistance and extensive application of carbon-ceramic materials are reduced, reduced particle emissions, and can be used with a wider range of pads.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005175251210000011
    Figure HDA0005175251210000011
  • Figure HDA0005175251210000012
    Figure HDA0005175251210000012
  • Figure HDA0005175251210000021
    Figure HDA0005175251210000021
Patent Text Reader

Abstract

The invention relates to a forming material comprising an inner layer made of a carbon-based material, referred to as "carbon-carbon" or "C / C", and a corresponding outer layer made of a carbon-ceramic material comprising carbon and silicon carbide, preferably said material being shaped to form a disc brake disc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a shaped material, a disk brake disk produced from the shaped material and a method for producing the shaped material. Background Art

[0002] The use of disc brake discs made of carbon-based materials, so-called "carbon-carbon" or "C / C", is well known. These are composite materials consisting of a carbon matrix in which reinforcing carbon fibers are arranged.

[0003] The discs made of "C / C" material are obtained by a process consisting of the superposition of layers or sheets of carbon fibers in the form of woven and / or non-woven fabrics, or the formation of so-called carbonaceous "preforms" using short fibers, possible addition of resin, possible subsequent heat treatment, and carbon densification. The latter can be carried out in various ways, for example by CVD (chemical vapor deposition), CVI (chemical vapor infiltration), LPI (liquid polymer infiltration), PIP (polymer infiltration and pyrolysis) or by impregnation with resins and / or pitch, all of which lead to an increase in density, thus giving the material adequate mechanical, thermal and tribological properties, for example, an increase in density of 2 to 6 times.

[0004] In order to function as a friction material, "C / C" materials require high application temperatures, which makes discs made of "C / C" materials particularly suitable for use in racing and aviation applications. Other characteristics of discs made of "C / C" materials that make them suitable for the above applications are low weight and high thermal conductivity.

[0005] However, the disk made of the "C / C" material has the following disadvantages.

[0006] Firstly, they are particularly subject to wear phenomena at the brake band. Besides inevitably affecting the durability of the disc, such wear phenomena also lead to the emission of carbon particulate matter into the atmosphere, with negative effects on the environment and human health.

[0007] Furthermore, such discs have a limited range of applications since they can only be used with carbon backings.

[0008] The use of disc brake discs made entirely of carbon-ceramic material is also known. They overcome the disadvantages of discs made of "C / C" material, are very durable, are hardly affected by wear phenomena, and can be used with a wider range of pads. They are typically used in high-performance road applications.

[0009] However, the disc made of carbon-ceramic material loses the advantageous characteristics associated with "C / C" materials, first of all, light weight. In addition, the disc made of carbon-ceramic material is more difficult to process and requires simpler geometry than the disc made of "C / C" material.

[0010] Therefore, the problem to be solved by the present invention is to provide a shaped material and a disc brake disc, which have both the advantageous features of a disc made of "C / C" material and the advantageous features of a disc made of carbon-ceramic material, and also provide a convenient and feasible method for obtaining the shaped material. Summary of the invention

[0011] The invention solves the above-mentioned problem by means of a shaped material, a method for its production and a disc brake disc made from said shaped material as outlined in the appended claims, the definitions of which form an integral part of the present description.

[0012] The present invention first relates to a forming material, which comprises:

[0013] an inner layer made of a carbon-based material called "carbon-carbon" or "C / C", and

[0014] The respective outer layers are made of a carbon-ceramic material including carbon and silicon carbide, namely a first outer layer and a second outer layer.

[0015] The present invention further relates to a disc brake disc made of the above-mentioned shaped material, the disc brake disc comprising:

[0016] a first braking band formed from said first outer layer of formed material, said first braking band being defined by a first braking surface for cooperating with a brake pad and by a corresponding inner surface;

[0017] a second braking band formed from said second outer layer of forming material, said second braking band being defined by a second braking surface for cooperating with a brake pad and by a corresponding inner surface;

[0018] A core is formed from the inner layer of formed material, the core extending between the inner surface of the first braking band and the inner surface of the second braking band.

[0019] The present invention also relates to a method for making the above-mentioned forming material, which method comprises the following steps in sequence:

[0020] a) preparing a carbon dense billet of a "C / C" material, the billet having two opposite surfaces, namely a first surface and a second surface;

[0021] b) optionally made into ventilation channels and / or feed channels characterizing a disc brake disc;

[0022] c) contacting the first surface and the second surface of the carbon dense billet of "C / C" material with silicon simultaneously or sequentially, so that at least a portion of the silicon penetrates the billet from the first surface to a predetermined thickness ("first thickness"), and penetrates the billet from the second surface to a predetermined thickness ("second thickness"), thereby obtaining a shaped material comprising the first outer layer and the second outer layer, the first outer layer and the second outer layer being made of a carbon-ceramic material comprising carbon and silicon carbide;

[0023] d) Optionally, the shaped material obtained in step c) is subjected to finishing.

[0024] The formed material of the invention and the corresponding disc brake disc advantageously have the lightness, thermal conductivity and processability typical of "C / C" materials, while exhibiting a high wear resistance, which allows a substantial reduction in particulate emissions into the atmosphere, with a positive impact on the environment and human health. Furthermore, the disc of the invention can advantageously be used with a wider range of pads, such as with sintered metal pads and pads with a ceramic matrix.

[0025] Further characteristics and advantages of the invention will become more apparent from the following description of some embodiments given by way of non-limiting example. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A cross-sectional view schematically shows a formed material for forming a disc brake disc according to an embodiment of the present invention.

[0027] Figure 2 A graph showing the weight increase of a disc made of "C / C" material with LSI performed on only one brake band and a disc made of "C / C" material with LSI performed on both brake bands is shown.

[0028] Figure 3 The images of the formed material according to the present invention obtained by SEM at different distances from the outer surface are shown (upper image: distance of about 4 mm from the surface; lower image: distance of about 8 mm from the surface), wherein the outer layer made of carbon-ceramic material has a thickness of about 8 mm. DETAILED DESCRIPTION

[0029] The present invention relates to a shaped material and a disc brake disc made from said shaped material, wherein the brake band is made of a carbon-ceramic material comprising carbon and silicon carbide, the outer surface of the brake band, the so-called braking surface, being suitable for cooperating with a pad of a disc brake, and the disc core defined by the inner surface of the brake band is made of a "C / C" carbonaceous material.

[0030] Since the brake bands defining the tribologically active part of the discs are made of carbon-ceramic material, they have greater mechanical strength and increased wear resistance, which prolongs the life of the discs and reduces particulate emissions into the environment. At the same time, the disc cores also maintain the properties that characterize "C / C" materials in terms of lightness and thermal conductivity, making the discs suitable for use in high-performance and sports car braking systems.

[0031] Figure 1 A cross-sectional view of a shaped material of the present invention is shown. More specifically, the material is shaped to form a disc brake disc, and the central hole of the disc is Figure 1 The cross section is indicated by a dotted line.

[0032] Figure 1 The forming material in the embodiment is indicated as a whole by reference numeral 1 and comprises or consists of the following items: an inner layer 2 made of a carbon-based "C / C" material; and two outer layers made of a carbon-ceramic material including carbon and silicon carbide (SiC), namely a first outer layer 3 and a second outer layer 4. Preferably, the outer layer 3 and the outer layer 4 have substantially the same thickness.

[0033] The first outer layer 3 forms a first braking band of the disc brake disc and is delimited by a first outer surface 5 (“first braking surface”) intended to cooperate with a brake pad and by a corresponding inner surface 6 .

[0034] The second outer layer 4 forms a second braking band of the disc brake disc and is delimited by a second outer surface 7 (“second braking face”) for cooperating with a brake pad and by a corresponding inner surface 8 .

[0035] The inner layer 2 forms a core which is delimited by the above-mentioned inner surfaces 6 and 8 of the brake band. In the inner layer 2, ventilation channels ( Figure 1 ); the ventilation channels can take variable and complex shapes and sizes, as they can also be made from a disposable core, but are preferably made by machining.

[0036] Advantageously, the inner layer 2 and the respective outer layers 3 , 4 extend substantially over the entire surface area of ​​the forming material 1 .

[0037] According to a first embodiment, the two outer layers 3, 4 of the forming material are made of a carbon-ceramic material comprising short, disordered filaments consisting essentially of carbon. Preferably, the filaments have a length of less than 30 mm, for example, the filaments have a length between 6 mm and 24 mm.

[0038] The term "filaments consisting essentially of carbon" refers to fiber materials typically produced from the pyrolysis of products of various synthetic sources such as polyacrylonitrile (PAN) or pitch.

[0039] The filaments are usually fiber bundles consisting of 3,000 to 50,000 fibers, wherein the diameter of a single fiber is generally 8 to 10 microns.

[0040] According to a second embodiment, the two outer layers 3, 4 of the forming material are made of a carbon-ceramic material consisting of spun fibers (yarns) and / or continuous fibers (tows) consisting essentially of carbon and arranged to form woven and / or non-woven fabrics.

[0041] The term "continuous long fibers" refers to fiber bundles having a high length-to-diameter ratio (typically in excess of 10,000:1). The term "spun fibers" refers to fiber bundles that have been spun to form a single yarn.

[0042] Preferably, the carbon-ceramic material of the outer layers 3, 4 comprises:

[0043] 10% to 40% carbon fiber, preferably about 15% to 30% carbon fiber;

[0044] 30% to 70% carbon matrix, preferably, about 40% to 60% carbon matrix;

[0045] 0% to 10% silicon, preferably about 0% to 5% silicon;

[0046] 10% to 40% SiC, preferably 20% to 30% SiC.

[0047] The above percentages are all weight percentages.

[0048] More preferably, the carbon-ceramic material of the outer layers 3, 4 comprises:

[0049] 15 to 25% by weight carbon fibers;

[0050] 45% to 55% by weight of a carbon matrix;

[0051] 3 to 4% by weight silicon;

[0052] 23 to 28% SiC by weight.

[0053] For the purpose of the present invention, the term "comprising" also includes the meaning of "consisting of" or "consisting essentially of."

[0054] Preferably, said outer layer 3, 4 of carbon-ceramic material has a porosity of less than 5%, or less than 4%, or less than 3%, or less than 2%.

[0055] Preferably, the outer layers 3, 4 of carbon-ceramic material have a carbon content of 1.7 g / cm 3 Up to 2.5g / cm 3Between or 1.8g / cm 3 Up to 2.4g / cm 3 Between or at 1.9g / cm 3 Up to 2.3g / cm 3 The density between.

[0056] Preferably, the "C / C" material of the inner layer 2 comprises:

[0057] 15% to 60% carbon fiber, preferably 20% to 40% carbon fiber;

[0058] 40% to 85% carbon matrix, preferably 60% to 80% carbon matrix.

[0059] The above percentages are all weight percentages.

[0060] For the purpose of the present invention, the term "comprising" also includes the meaning of "consisting of" or "consisting essentially of."

[0061] Preferably, said inner layer 2 made of "C / C" material has a porosity between 5% and 20%, or between 5% and 10%.

[0062] Preferably, the inner layer 2 made of "C / C" material has a strength of 1.5 g / cm 3 Up to 1.9g / cm 3 Between or 1.6g / cm 3 Up to 1.8g / cm 3 The density between.

[0063] Such porosity and density values ​​of the inner layer 2 made of "C / C" material make the formed material lighter.

[0064] The porosity of the outer layers 3, 4 and the inner layer 2 is measured in water using the hydrostatic weighing technique according to ISO 18754:2020 standard.

[0065] The densities of the outer layers 3, 4 and the inner layer 2 are measured in terms of geometric dimensions.

[0066] Preferably, the thickness of each of the outer layers 3, 4 is at least 4%, or at least 4.5%, or at least 5% of the thickness of the formed material.

[0067] Preferably, the thickness of each of the outer layers 3, 4 does not exceed 25% of the thickness of the formed material, or does not exceed 20% of the thickness of the formed material, or does not exceed 15% of the thickness of the formed material, or does not exceed 10% of the thickness of the formed material.

[0068] According to a preferred embodiment, the thickness of each of the outer layers 3, 4 is between 0.5 mm and 10 mm. Preferably, the thickness is at least 1 mm, or at least 2 mm, or at least 3 mm, or at least 4 mm. Preferably, the thickness does not exceed 8 mm, or does not exceed 7 mm, or does not exceed 6 mm. For example, the thickness is between 2 mm and 8 mm, or between 4 mm and 8 mm.

[0069] The above-mentioned thickness values ​​of the outer layers 3, 4 are intended to be average values, which means that said layers do not necessarily have the same thickness over the entire surface area of ​​the shaped material. For example, close to the edges of the shaped material, the thickness of the outer layers may be greater; said variability of thickness may be about ±2 mm. This is all the more evident with reference to the method for producing a shaped material according to the invention, said method comprising a step of infiltrating silicon into a "C / C" material, as will be described hereinafter. During said infiltration step, the rise of silicon by capillary action may be greater at the edges, due to the inhomogeneity of the microstructure of the material, as well as to edge effects in the lateral areas of the material.

[0070] The outer layers 3, 4 of the shaped material forming the brake band of a disc brake disc are subject to wear. The thickness of said layers must therefore be such as to withstand the wear phenomena in order to avoid exposure of the underlying "C / C" material, ensuring as long a service life of the disc as possible. At the same time, the thickness of said layers must not be too great, otherwise the material would become too heavy. The abovementioned thickness values ​​are a suitable compromise between these two aspects.

[0071] Preferably, the thickness of the inner layer 2 is at least 50%, or at least 55%, or at least 60%, or at least 65%, or at least 70%, or at least 75% of the thickness of the formed material.

[0072] Preferably, the thickness of the inner layer 2 does not exceed 92% of the thickness of the formed material, or does not exceed 90% of the thickness of the formed material, or does not exceed 85% of the thickness of the formed material, or does not exceed 80% of the thickness of the formed material.

[0073] Advantageously, the forming material of the present invention is monolithic in that it is formed from a single piece of "C / C" material, as will become more apparent hereinafter in the description of its method of manufacture.

[0074] The shaped material of the present invention is obtained by the method according to the claim. In particular, the method comprises the following steps in sequence:

[0075] a) preparing a carbon dense billet of a "C / C" material, the billet having two opposite surfaces, namely a first surface and a second surface;

[0076] b) optionally made into ventilation channels and / or feed channels characterizing a disc brake disc;

[0077] c) contacting the first surface and the second surface of the carbon dense billet of "C / C" material with silicon simultaneously or sequentially, so that at least a portion of the silicon penetrates the billet from the first surface to a predetermined thickness (also referred to as "first thickness" in the present application), and penetrates the billet from the second surface to a predetermined thickness (also referred to as "second thickness" in the present application), thereby obtaining a shaped material comprising the first outer layer and the second outer layer, the first outer layer and the second outer layer being made of a carbon-ceramic material comprising carbon and silicon carbide;

[0078] d) Optionally, the shaped material obtained in step c) is subjected to finishing.

[0079] The phrase "carbon densified billet of "C / C" material", also referred to as "blanket" or "C / C billet" in this application, means a preform made of "C / C" material which has undergone a carbon densification process, as will become more apparent from the description below.

[0080] Step a) of the method of the present invention

[0081] First embodiment

[0082] According to a first embodiment, during said step a), a carbon dense blank of "C / C" material is prepared from a corresponding preform, the carbon dense blank comprising spun fibers (yarns) and / or continuous long fibers (tows) essentially consisting of carbon and arranged to form a woven fabric and / or a non-woven fabric. The preparation of said preform is carried out by known methods. An example is described in WO2019 / 180550.

[0083] According to an embodiment, said step a) of preparing a carbon dense blank of "C / C" material comprises the following steps in sequence:

[0084] i) stacking carbon or carbon precursor fiber layers in the form of woven fabrics and / or non-woven fabrics to form a preform mold;

[0085] ii) needle punching the stacked fiber layers to form a three-dimensional interwoven structure;

[0086] iii) optionally, carbonizing the carbon precursor fibers into carbon fibers;

[0087] iv) optionally, impregnating the preform mold obtained in step i), step ii) or step iii) with a resin;

[0088] v) optionally, thermally pretreating the preform obtained in one of step i), step ii), step iii) or step iv);

[0089] vi) subjecting the preform obtained in one of step ii), step iii), step iv) or step v) to carbon densification, preferably until the material density exceeds 1.5 g / cm 3 or more than 1.7g / cm 3 , to form a carbon dense billet of "C / C" material;

[0090] vii) heat treating the blank obtained in step vi).

[0091] In step i), the layer may comprise carbon fibers (i.e. fibers that have been carbonized) or precursors of such carbon fibers (preferably PAN, pitch or rayon) which are converted into carbon fibers during a carbonization step iii) after needling. Carbonization typically comprises heating the fibers to a temperature between 1500° C. and 2000° C., the temperature varying according to the type of precursor.

[0092] According to an embodiment, the preform mold is cylindrical in shape, with its axis parallel to the stacking axis of the fiber layers.

[0093] The needling in step ii) can be performed using conventional methods, including the use of appropriate needles which engage parts of the fibers by guiding them axially, thereby allowing a three-dimensional structure to be obtained.

[0094] For example, the resin used in the impregnation step iv) is selected from the following: phenolic resins, acrylic resins, polystyrene resins, furan resins, or cyanoesters.

[0095] The heat treatment in step v) and step vii) renders the material highly thermally conductive. Preferably, such heat treatment comprises treatment in an inert atmosphere or in a vacuum furnace up to a temperature between 800°C and 2550°C.

[0096] Second embodiment

[0097] According to a second embodiment, during said step a), a carbon dense billet of "C / C" material is prepared, comprising short and disordered filaments consisting essentially of carbon, wherein said filaments preferably have a length less than 30 mm, for example a length between 6 mm and 24 mm. The preparation of said billet is carried out by known methods.

[0098] According to an embodiment, said step a) of preparing a carbon dense blank of "C / C" material comprises the following steps in sequence:

[0099] i) printing short carbon fibers or carbon precursor fibers mixed with a resin to form a preform pattern, wherein the resin is preferably phenolic resin, acrylic resin, paraffin, asphalt, furan resin, or polystyrene;

[0100] ii) pyrolyzing the preform obtained in step i);

[0101] iii) subjecting the preform obtained in step ii) to a carbon densification treatment, preferably until the material density exceeds 1.5 g / cm 3 or more than 1.7g / cm 3 , to form a carbon dense billet of "C / C" material;

[0102] iv) heat treating the blank obtained in step iii).

[0103] During step i), the carbon fibers or a precursor of such carbon fibers, preferably PAN, pitch or rayon, may be shaped. The shaping step i) is preferably carried out by operating at a temperature between 80° C. and 200° C., preferably between 120° C. and 180° C. and / or at a pressure between 5 and 250 bar, preferably between 5 and 100 bar.

[0104] The preform model removed from the mold undergoes a pyrolysis step ii) in order to carbonize the binding resin. Preferably, step ii) is carried out in a conventional furnace at a temperature, depending on the type of resin used, generally between 800° C. and 1000° C. Advantageously, the pyrolysis step ii) is carried out under a flow of an inert gas such as nitrogen or argon and at a pressure preferably between 10 mbar and 1000 mbar, preferably between 500 mbar and 1000 mbar. The inert gas flow also has the function of advantageously removing the gases released by the pyrolysis of the resin.

[0105] The heat treatment in step iv) renders the material highly thermally conductive and preferably comprises a treatment in an inert atmosphere or in a vacuum furnace up to a temperature between 1800° C. and 2550° C.

[0106] According to different embodiments, carbon densification of preforms comprising spun fibers and / or continuous fibers arranged to form a woven or non-woven fabric (the first embodiment described above) and preforms comprising short and disordered filaments (the second embodiment described above) is performed by different methods.

[0107] The first method is CVD (chemical vapor deposition) or CVI (chemical vapor infiltration), depending on whether only a coating is performed or carbon infiltration is performed in the gas phase. Typically, if the material is fibrous and therefore has a high porosity, chemical vapor infiltration (CVI) is used. These methods involve the use of a hydrocarbon mixture (such as methane and propane) and exposing the material to be treated to such a mixture at high temperature and low pressure. The operating temperature is about 900°C to 1200°C, preferably 1000°C to 1100°C, and the operating pressure is less than 300 millibars, preferably tens of millibars. The hydrocarbon mixture decomposes to form carbon elements, which are then deposited or infiltrated into the matrix of the material to be treated. This method, which requires the use of a dedicated furnace, involves the deposition of a thin layer (typically a few microns) on the fiber, whereby several infiltration cycles are required and the total coating on the fiber exceeds 10 microns (typically 20 to 30 microns) to obtain the desired density.

[0108] A different method, called LPI (Liquid Polymer Infiltration) or PIP (Polymer Infiltration and Pyrolysis), consists in infiltrating the matrix of the material to be treated with a liquid polymer, followed by a heat treatment at high temperature (pyrolysis), which carbonizes the polymer deposited on the carbon fibers. Again, several infiltration and pyrolysis steps are required before adequate densification of the preform is obtained.

[0109] Regardless of the method used in the carbon densification step, the material density of the resulting billet is typically greater than 1.5 g / cm 3 .

[0110] Step b) of the method of the present invention (optional)

[0111] In step b), the carbon dense billet of "C / C" material obtained in step a) is subjected to preliminary processing or pre-processing.

[0112] Said step b) may comprise a step of shaping the blank, i.e. the dense preform, during which the blank is cut to the almost finished shape and size of the disc brake disc. Alternatively, the shaping operation is carried out on the individual fiber layers before the superposition step i) or the needling step ii), or on the needling multilayer downstream of step ii). Optionally, said shaping step is carried out in the case of a blank obtained from a preform comprising spun fibers and / or continuous fibers; the preform comprising short and disordered fibers can be given the desired shape in a suitable mold.

[0113] During said step b), the ventilation channels and / or feed channels of the ventilated brake disc are also made. By "feed channels" are meant holes through which the bell of the disc can then be attached.

[0114] Step c) of the method of the present invention

[0115] During step c) of the method for manufacturing a shaped material according to the invention, the two surfaces of the carbon dense blank of "C / C" material optionally subjected to said step b) are brought into contact with silicon.

[0116] According to a first embodiment, the first and second surfaces of the blank are contacted with silicon simultaneously. In this embodiment, the silicon simultaneously penetrates the blank from the first surface to a predetermined thickness ("first thickness") and from the second surface to a predetermined thickness ("second thickness") to form two outer layers 3, 4 of the formed material.

[0117] According to a second embodiment, the first surface and the second surface of the blank are contacted with silicon in sequence. This means that firstly the first surface of the blank is contacted with silicon, so that at least a portion of the silicon penetrates the blank from the first surface to a predetermined thickness ("first thickness") to form a first outer layer 3 of the formed material; then the second surface of the blank is contacted with silicon, so that at least a portion of the silicon penetrates the blank from the second surface to a predetermined thickness ("second thickness") to form a second outer layer 4 of the formed material.

[0118] Preferably, the penetration thickness of silicon from the first surface ("first thickness") and from the second surface ("second thickness") is at least 4%, or at least 4.5%, or at least 5% of the thickness of the ingot.

[0119] Preferably, the penetration thickness of silicon from the first surface ("first thickness") and the penetration thickness from the second surface ("second thickness") do not exceed 25% of the thickness of the ingot, or do not exceed 20% of the thickness of the ingot, or do not exceed 15% of the thickness of the ingot, or do not exceed 10% of the thickness of the ingot.

[0120] Preferably, the first thickness and the second thickness are substantially the same.

[0121] According to a first embodiment (silicon infiltration from both surfaces simultaneously), said step c) comprises the following steps:

[0122] c1) placing the side of the first surface of the blank on a first layer comprising silicon, preferably solid silicon, and depositing a second layer comprising silicon, preferably solid silicon, on a second surface of the blank opposite to the first surface;

[0123] c2) subjecting the ingot in contact with said first and second layers comprising silicon to a temperature such that at least a portion of the silicon penetrates the ingot by capillary action to said first and second thicknesses.

[0124] According to a second embodiment (silicon infiltration from two surfaces in sequence), step c) comprises the following steps:

[0125] c1) placing the first surface of the blank on its side on a first layer comprising silicon, preferably solid silicon;

[0126] c2) subjecting the ingot resting on said first layer comprising silicon to a temperature such that at least a portion of the silicon penetrates the ingot by capillary action to said first thickness;

[0127] c1-bis) placing the second surface of the material obtained in step c2) on a second layer comprising silicon, preferably solid silicon;

[0128] c2-bis) subjecting a material resting on said second layer comprising silicon to a temperature such that at least a portion of the silicon penetrates the material by capillary action to said second thickness.

[0129] In an embodiment, the above-mentioned layer comprises solid silicon. In addition to solid silicon, the layer may also include one or more materials, such as boron carbide (B4C). According to this embodiment, the boron carbide is present in the layer in a weight percentage preferably between 5% and 50%, more preferably between 5% and 20%.

[0130] In another embodiment, the above-mentioned layer consists of solid silicon.

[0131] The solid silicon may be in pure form or in a silicon / aluminum or silicon / copper alloy, and may be granular or powder.

[0132] In the following, the term "silicon layer" is used both with reference to a layer comprising solid silicon and with reference to a layer consisting of solid silicon.

[0133] According to an embodiment, during step c1) and step c1-bis), the material rests directly on the silicon layer. The term "directly" relates to the fact that the material is in contact with the silicon layer and there are no additional devices or elements between the material and the silicon layer.

[0134] According to another embodiment, during steps c1) and c1-bis), the material rests on the silicon layer by external means or elements, for example by porous partitions, such as felt, pyrolyzed wood elements or nails. In this embodiment, during steps c1) and c1-bis), the material does not come into contact with the silicon in the embedding layer; in the subsequent infiltration steps c2) and c2-bis), the material will come into contact with the silicon.

[0135] Preferably, the silicon infiltration step c2) and the silicon infiltration step c2-bis) are carried out in a suitable treatment chamber provided with ventilation openings for gases released during the treatment.

[0136] The infiltration step c2) and the infiltration step c2 bis) advantageously comprise an LSI (liquid silicon infiltration) process, during which the silicon layer is subjected to a temperature above the melting temperature of silicon, preferably above 1410°C, more preferably between 1420°C and 1700°C, so that the silicon melts and infiltrates the preform by capillary action to said first thickness and said second thickness.

[0137] According to this embodiment, the treatment chamber is preferably introduced into a suitable conventional furnace, which is heated at the above-mentioned temperature, for example, at about 1500°C. At this temperature, the silicon melts and penetrates the pores of the surface in contact with the silicon and reacts with some of the carbon in the carbon fibers and / or carbon matrix to form silicon carbide (SiC). Preferably, a portion of the molten silicon reacts with the carbon to form silicon carbide, and a portion of the silicon remains unreacted. The unreacted silicon solidifies in the material during the cooling step. The heating to the treatment temperature and the subsequent cooling are both carried out stepwise. For example, it may take 8 hours or more to reach a treatment temperature of about 1500°C, and a similar amount of time is required to cool the infiltrated material.

[0138] Preferably, the silicon infiltration step c2) and the silicon infiltration step c2-bis) are carried out at a pressure between 20 and 150 mbar, more preferably at a reduced pressure between 80 and 120 mbar.

[0139] As an alternative to the above process (comprising deposition of material on the silicon layer and silicon infiltration by LSI), step c) of the method of the present invention may comprise impregnating the blank with a silicone resin. According to this alternative embodiment, the blank is immersed in a silicone resin bath on the side of the first surface to a thickness substantially equal to the first thickness, and then the blank is subjected to an impregnation step at a maximum temperature of 80°C, followed by a resin polymerization step at a maximum temperature of 150°C, and finally a pyrolysis step at a temperature between 800°C and 1000°C to convert the resin into a ceramic material; the impregnation temperature and the polymerization temperature vary depending on the type of resin. The resulting material is then immersed in a silicone resin bath on the side of the second surface to a thickness substantially equal to the second thickness, and the same impregnation step, polymerization step and pyrolysis step are repeated.

[0140] Preferably, the amount of silicon in contact with each of the first and second surfaces of the billet is between 2% and 15% by weight, or between 3% and 12% by weight, or between 4% and 10% by weight, or between 5% and 7.5% by weight, relative to the weight of the billet.

[0141] The amount of silicon is such as to ensure that the silicon penetrates into the above-mentioned first thickness and the second thickness. In particular, the amount of silicon is the amount required to at least partially fill the pores of the "C / C" material of the blank from the first surface to a thickness equal to the first thickness, and to at least partially fill the pores of the "C / C" material of the blank from the second surface to a thickness equal to the second thickness. In particular, the amount of silicon is such that it does not fill the pores of the inner layer made of "C / C" material extending between the above-mentioned first thickness and the second thickness.

[0142] The method of making the forming material of the present invention as described above enables the two outer layers made of carbon-ceramic material to have a non-homogeneous composition throughout their thickness; for example, the concentration of silicon and silicon carbide can be higher near the two outer surfaces, and the concentration of silicon and silicon carbide gradually decreases as it moves away from the surface.

[0143] It was found that the carbon dense blank of the "C / C" material was completely absorbed by the silicon it came into contact with. This means that the absorption of silicon by the blank is quantitative. This advantageously allows the infiltration thickness to be controlled by also adjusting the amount of silicon. In this regard, Figure 2 Graphs showing weight gain of a carbon compact billet of "C / C" material with LSI performed on only one surface (left histogram) and on both surfaces (right histogram) in a single infiltration step are shown. The "target" is the amount of silicon used in contact with a surface.

[0144] For example, the infiltration thickness of the silicon is monitored by analyzing sections of the formed material using SEM microscopy. Figure 3 Two images obtained by SEM of a shaped material according to the invention at different distances from the outer surface are shown, wherein the outer layer made of carbon-ceramic material has a thickness of about 8 mm.

[0145] Figure 3 An image obtained by SEM at about 4 mm from the outer surface is shown (at the top). It can be clearly seen that all carbon pores (dark grey) are filled with silicon and silicon carbide (light grey), so the material is a carbon-ceramic.

[0146] Figure 3 An image obtained by SEM at greater depth is shown (at the bottom). At about 8 mm from the surface, the interface between the outer layer of material infiltrated with silicon and the inner layer made of "C / C" material can be clearly seen. This shows that with increasing depth, the material becomes "C / C" material again.

[0147] Experiments have also confirmed that the thermal conductivity of the formed material of the invention remains substantially the same as that of the "C / C" material (70 W / mK) at 600° C. This means that ceramization does not change the material very significantly from a thermal point of view.

[0148] Step d) of the method of the present invention (optional)

[0149] During step (d), the material obtained in step c) undergoes a second machining or finishing process, during which the material is brought to the finished shape and / or size of the disc brake disc. A final machining is usually necessary since the heat treatment may deform the shape of the formed material. During step d), any surface deformations are then eliminated. Such a finishing process is preferably carried out dry, for example by means of a diamond grinding wheel.

[0150] Obviously, only one particular embodiment of the invention has been described. A person skilled in the art will be able to make all necessary modifications to the shaped material and the method for obtaining the shaped material of the invention to adapt it to the specific conditions without departing from the scope of protection defined in the appended claims.

Claims

1. A forming material (1), comprising: an inner layer (2) made of a carbon-based material known as "carbon-carbon" or "C / C", and The corresponding outer layers are made of a carbon-ceramic material including carbon and silicon carbide, and the corresponding outer layers are respectively a first outer layer (3) and a second outer layer (4).

2. The material according to claim 1, wherein The first outer layer (3) and the second outer layer (4) are made of a carbon-ceramic material comprising short and disordered filaments essentially consisting of carbon, wherein, preferably, the filaments have a length of less than 30 mm, for example, the filaments have a length between 6 mm and 24 mm.

3. The material according to claim 1, wherein The first outer layer (3) and the second outer layer (4) are made of a carbon-ceramic material comprising spun fibers (yarns) and / or continuous fibers (tows) essentially consisting of carbon and arranged to form woven and / or non-woven fabrics.

4. A material according to any one of the preceding claims, wherein The carbon-ceramic material of the first outer layer (3) and the second outer layer (4) comprises: 10% to 40% carbon fiber, preferably about 15% to 30% carbon fiber; 30% to 70% carbon matrix, preferably, about 40% to 60% carbon matrix; 0% to 10% silicon, preferably about 0% to 5% silicon; 10% to 40% SiC, preferably 20% to 30% SiC; The percentages are by weight.

5. A material according to any one of the preceding claims, wherein The first outer layer (3) and the second outer layer (4) have a porosity of less than 5%, or less than 4%, or less than 3%, or less than 2%, and / or the first outer layer (3) and the second outer layer (4) have a porosity of less than 1.7 g / cm 3 Up to 2.5g / cm 3 Between or 1.8g / cm 3 Up to 2.4g / cm 3 Between, or 1.9g / cm 3 Up to 2.3g / cm 3 The density between.

6. A material according to any one of the preceding claims, wherein The "C / C" material of the inner layer (2) comprises: 15% to 60% carbon fiber, preferably 20% to 40% carbon fiber; 40% to 85% carbon matrix, preferably 60% to 80% carbon matrix; The percentages are by weight.

7. A material according to any one of the preceding claims, wherein The inner layer (2) has a porosity between 5% and 20%, preferably, the inner layer (2) has a porosity between 5% and 10%, and / or the inner layer (2) has a porosity between 1.5 g / cm 3 Up to 1.9g / cm 3 Preferably, the inner layer (2) has a density between 1.6 g / cm 3 Up to 1.8g / cm 3 The density between.

8. A material according to any one of the preceding claims, wherein The thickness of each of the outer layers (3, 4) is at least 4%, or at least 4.5%, or at least 5% of the thickness of the forming material, and / or the thickness of each of the outer layers (3, 4) does not exceed 25% of the thickness of the forming material, or does not exceed 20% of the thickness of the forming material, or does not exceed 15% of the thickness of the forming material, or does not exceed 10% of the thickness of the forming material.

9. The material according to claim 8, wherein The thickness of each of the outer layers (3, 4) is between 0.5 mm and 10 mm, preferably, the thickness of each of the outer layers (3, 4) is between 2 mm and 8 mm, or between 4 mm and 8 mm.

10. A material according to any one of the preceding claims, wherein The thickness of the inner layer (2) is at least 50%, or at least 55%, or at least 60%, or at least 65%, or at least 70%, or at least 75% of the thickness of the forming material, and / or the thickness of the inner layer (2) does not exceed 92% of the thickness of the forming material, or does not exceed 90% of the thickness of the forming material, or does not exceed 85% of the thickness of the forming material, or does not exceed 80% of the thickness of the forming material.

11. A material according to any one of the preceding claims, wherein The material is shaped to form a disc brake disc.

12. A disc brake disc made of the shaped material according to any one of claims 1 to 11, the disc brake disc comprising: a first braking band formed by said first outer layer (3) of said forming material, said first braking band being delimited by a first braking surface (5) for cooperating with a brake pad and a corresponding inner surface (6); a second braking band formed by said second outer layer (4) of said forming material, said second braking band being delimited by a second braking surface (7) for cooperating with a brake pad and a corresponding inner surface (8); A core is formed by the inner layer (2) of the forming material, the core extending between the inner surface (6) of the first braking band and the inner surface (8) of the second braking band.

13. A method for producing a shaped material according to any one of claims 1 to 11, the method comprising the following steps in sequence: a) preparing a carbon dense billet of a "C / C" material, the billet having two opposite surfaces, the two opposite surfaces being a first surface and a second surface respectively; b) optionally made into ventilation channels and / or feed channels characterizing a disc brake disc; c) contacting the first surface and the second surface of the carbon dense billet of "C / C" material with silicon simultaneously or sequentially, so that at least a portion of the silicon penetrates the billet from the first surface to a predetermined thickness ("first thickness"), and penetrates the billet from the second surface to a predetermined thickness ("second thickness"), thereby obtaining a shaped material, the shaped material comprising the first outer layer and the second outer layer, the first outer layer and the second outer layer being made of a carbon-ceramic material comprising carbon and silicon carbide; d) Optionally, the shaped material obtained in step c) is subjected to finish machining.

14. The method according to claim 13, wherein: The silicon penetration thickness from the first surface and from the second surface is at least 4%, or at least 4.5%, or at least 5% of the thickness of the carbon dense preform, and / or the silicon penetration thickness from the first surface and from the second surface does not exceed 25% of the thickness of the billet, or does not exceed 20% of the thickness of the billet, or does not exceed 15% of the thickness of the billet, or does not exceed 10% of the thickness of the billet.

15. The method according to claim 13 or 14, wherein: During said step a), a carbon compact billet made of a "C / C" material is prepared, said carbon compact billet comprising spun fibres (yarns) and / or continuous fibres (tows) consisting essentially of carbon and arranged to form woven and / or non-woven fabrics.

16. The method according to claim 15, wherein: The step a) of preparing the carbon dense blank made of "C / C" material comprises the following steps in sequence: i) stacking carbon or carbon precursor fiber layers in the form of woven fabrics and / or non-woven fabrics to form a preform mold; ii) needle punching the stacked fiber layers to form a three-dimensional interwoven structure; iii) optionally, carbonizing the carbon precursor fibers into carbon fibers; iv) optionally, impregnating the preform mold obtained in step i), step ii) or step iii) with a resin; v) optionally, thermally pretreating the preform obtained in one of step i), step ii), step iii) or step iv); vi) subjecting the preform obtained in one of step ii), step iii), step iv) or step v) to carbon densification to form a carbon densified blank made of "C / C" material, preferably, subjecting the preform obtained in one of step ii), step iii), step iv) or step v) to carbon densification until the material density exceeds 1.5 g / cm 3 or more than 1.7g / cm 3 , to form a carbon dense billet made of "C / C" material; vii) heat treating the blank obtained in step vi).

17. The method according to claim 13 or 14, wherein: During said step a), a carbon dense billet made of "C / C" material is prepared, said carbon dense billet comprising short and disordered filaments essentially consisting of carbon, wherein, preferably, said filaments have a length of less than 30 mm, for example, said filaments have a length between 6 mm and 24 mm.

18. The method according to claim 17, wherein: The step a) of preparing the carbon dense blank made of "C / C" material comprises the following steps in sequence: i) molding short carbon fibers or carbon precursors mixed with resin to form a preform mold, preferably, the resin is phenolic resin, acrylic resin, paraffin, asphalt, furan resin, or polystyrene; ii) pyrolyzing the preform obtained in step i); iii) subjecting the preform model obtained in step ii) to carbon densification to form a carbon densified blank made of "C / C" material, preferably, subjecting the preform model obtained in step ii) to carbon densification until the material density exceeds 1.5 g / cm 3 or more than 1.7g / cm 3 , to form a carbon dense billet made of "C / C" material; iv) heat treating the blank obtained in step iii).

19. The method according to any one of claims 13 to 18, wherein: The amount of silicon in contact with each of the first surface and the second surface of the carbon dense preform is between 2% and 15% by weight, or between 3% and 12% by weight, or between 4% and 10% by weight, or between 5% and 7.5% by weight, relative to the weight of the preform.

20. The method according to any one of claims 13 to 19, wherein: Step c) comprises the following steps: c1) resting the first surface of the blank on a first layer comprising silicon, preferably solid silicon, and depositing a second layer comprising silicon, preferably solid silicon, on a second surface of the blank opposite to the first surface; and c2) subjecting the ingot in contact with the first layer and the second layer comprising silicon to a temperature such that at least a portion of the silicon penetrates the ingot by capillary action to the first thickness and the second thickness.

21. The method according to claim 20, wherein: Step c2) includes: performing a liquid silicon infiltration (LSI) process at a temperature above the melting temperature of silicon, preferably, performing the liquid silicon infiltration (LSI) process at a temperature above 1410°C, more preferably, performing the liquid silicon infiltration (LSI) process at a temperature between 1420°C and 1700°C, and / or preferably, performing the liquid silicon infiltration (LSI) process at a pressure between 20 mbar and 150 mbar, more preferably, performing the liquid silicon infiltration (LSI) process at a pressure between 80 mbar and 120 mbar.

22. The method according to any one of claims 13 to 19, wherein: Step c) comprises the following steps: c1) placing the first surface of the blank on the first layer comprising silicon, preferably placing the first surface of the blank on the first layer comprising solid silicon; c2) subjecting said blank resting on said first layer comprising silicon to a temperature such that at least a portion of the silicon penetrates said blank by capillary action to said first thickness; c1-bis) placing the side of the second surface of the material obtained from step c2) on a second layer comprising silicon, preferably placing the side of the second surface of the material obtained from step c2) on a second layer comprising solid silicon; c2-bis) subjecting said material resting on said second layer comprising silicon to a temperature such that at least a portion of the silicon penetrates said material by capillary action to said second thickness.

23. The method according to claim 22, wherein: Step c2) and step c-2 bis) include: performing a liquid silicon infiltration (LSI) process at a temperature above the melting temperature of silicon, preferably, performing the liquid silicon infiltration (LSI) process at a temperature above 1410°C, more preferably, performing the liquid silicon infiltration (LSI) process at a temperature between 1420°C and 1700°C, and / or preferably, performing the liquid silicon infiltration (LSI) process at a pressure between 20 mbar and 150 mbar, more preferably, performing the liquid silicon infiltration (LSI) process at a pressure between 80 mbar and 120 mbar.

24. A shaped material obtainable by a method according to any one of claims 13 to 23.

Citation Information

Patent Citations

  • Method of making a fibrous preform and a fibrous preform thus obtained

    WO2019180550A1